2012
DOI: 10.1007/s11270-012-1114-8
|View full text |Cite
|
Sign up to set email alerts
|

Scots Pine (Pinus sylvestris L.) Growth Suppression and Adverse Effects on Human Health Due to Air Pollution in the Upper Silesian Industrial District (USID), Southern Poland

Abstract: Air pollution emissions were not continually monitored in the Upper Silesian Industrial District (USID), southern Poland, and data is only available for the last 20 years. Long-lasting and severe tree ring reductions in pines growing 5–20 km north of the USID area recorded particularly high levels of air pollution emissions in the period 1950–1990. Especially high amounts of reductions and many missing rings were found in the period 1964–1981. At the same time, pines growing 60 km west of the USID do not recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
(30 reference statements)
3
24
0
Order By: Relevance
“…The biological effects of pollutants stress on trees depend on the species and age of trees and the habitat condition where they grow (e.g. ; Danek 2007;Malik et al, 2012;Sensuła et al, 2015aSensuła et al, , 2015b.…”
Section: Trees As Bio-indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological effects of pollutants stress on trees depend on the species and age of trees and the habitat condition where they grow (e.g. ; Danek 2007;Malik et al, 2012;Sensuła et al, 2015aSensuła et al, , 2015b.…”
Section: Trees As Bio-indicatorsmentioning
confidence: 99%
“…Different methods of dendrochronological analysis were often used to evaluate the impact of pollution on the potential incremental trees (McLaughlin et al, 2002;Bascietto et al, 2004;Battipaglia et al, 2009;Eckstein and Schweingruber, 2009), A number of studies have investigated: the rate of trees with different degrees of growth reduction to the diameter and height (Kienast, 1985;Schweingruber, 1986;Danek, 2007;Elling et al, 2009;Malik et al, 2012;Crecente-Campo et al, 2010), differences in similarity in radial growth response of trees (Wilczynski, 2006). Scientific literature reviews have shown that, the size of reduction also depends on the distance from the source of pollution, directions prevailing winds and area orography (Krąpiec and Szychowska Krąpiec, 2001;Juknys et al, 2003Juknys et al, , 2014Wilczyński, 2006;Elling et al, 2009;Malik et al, 2012;Rydval and Wilson, 2012;Bošela et al, 2014).…”
Section: Trees As Bio-indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the negative impact of pollution on trees can be varied in space and depends on the habitat conditions and distance from the source of pollution, directions of prevailing winds (Wilczyński, 2006;Danek, 2007;Elling et al, 2009;Malik et al, 2012). The trees, growing under stress of the pollutants, reduce their radial growth and height growth (Kienast, 1985, Schweingruber, 1986Krąpiec and Szychowska-Krapiec, 2001;Danek, 2007;Elling et al, 2009;Malik et al, 2012;Crecente-Campo et al, 2010). Also the differences in the similarity of radial growth response of pines to individual climate factors (temperature, sunshine, precipitation, air humidity) has been observed (for example Sensula et al, 2015aSensula et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Trees are another source of long-term data on pollution (e.g. Stravinskiene et al, 2013, Malik et al, 2012. Annual growth rings of trees have the potential to record and preserve annually resolved metal concentrations from atmospheric and soil sources, a technique known as dendrochemistry (Watmough, 1999, McLaughlin et al, 2002.…”
Section: Introductionmentioning
confidence: 99%